Analytical investigation on the buckling and free vibration of porous laminated FG-CNTRC plates - Ghazoul, Tahir; Benatta, Mohamed Atif; Khatir, Abdelwahhab; Beldjelili, Youcef; Krour, Baghdad; Bachir Bouiadjra, Mohamed (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The aim of this study is to examine the buckling and free vibration behavior of laminated composite plates reinforced with carbon nanotubes when various sources of uncertainty are taken into account with the main focus being the existence of porosity. Methods: A porous laminated plate model is developed using a high order shear deformation theory. Different configurations of functionally graded aligned single-walled carbon nanotubes throughout the thickness of each layer are being investigated. The effective properties of materials are evaluated through the extended rule of mixture while considering an upper bound for the effect of porosity. The governing equations are derived and solved using the virtual work principle and Navier’s approach. The validity of the current formulation is confirmed by comparing the results with the existing data from literature sources. The impact of numerous parameters such as porosity, carbon nanotube volume fraction, reinforcement distribution types, lamination scheme, and the number of layers on the buckling and free vibration responses is investigated in detail. Results: A key finding of this study is the significant reduction in buckling resistance of laminated FG-CNTRC plates due to porosity, contrasting with the minor impact on the free vibration response. Conclusion: The results of this paper emphasize the critical role of porosity in structural integrity and provide novel insights into the behaviour of advanced composite materials.